PERBANDINGAN NILAI BIOLOGIS PAKAN LOKAL DAN IMPOR PADA ANAK KUDA PACU INDONESIA - Manarisip, Cicilia M; Tulung, Y L.R; Kaunang, W B; Tuturoong, R A.V (Universitas Sam Ratulangi, 2017)
ABSTRACT COMPARISON OF BIOLOGICAL VALUE OF LOCAL AND IMPORT FEED IN INDONESIAN CHILD RACE HORSE. This research aims to determine the livestock child race horse's ability to digest feed, both local and imported feed. Digestibility of nutrients is a factor that determines the quality of feed ingredients or feed consumed by the livestock horses. This research used Statistics t-test method.Techniques of data retrieval are interviews and direct observations at sites of breeding racehorses. Data collected ie the type of local feed (corn, rice bran, fish meal, soybean, mung beans, coconut cake) and the types of imported feed (sustaina). The amount of feed (forage and concentrates) were given to livestock of child racehorse obtain the amount of feces (g / head / day) is then taken as many as 12 samples each of 8 racehorses using local feed and 4 racehorses use imported feed. The variables measured are digestibility of energy and protein digestibility. The results of the research are digestible energy (local feed ± 85.92 and imported feed ± 87.58) and protein digestibility (local feed ± 75.86 and imported feed 86.89 ±). T test, showed that the energy digestibility of feed imports give effect not significantly different (P> 0.05) compared to local feed while the digestibility of protein feed imports significantly different (P <0.01) in comparison with the local feed. Based on these results it can be concluded that the digestibility of protein for imported feed better than the local feed. Keywords: livestock horses, local feed, imported feed, digestibility